(untitled) (Global Journal of Human-Social Science, 2023)
This contribution analyzes the poetic writing of Ondjaki born Ndalu de Almeida following the approach developed in Degli Atti 2023 In the context of the perspective we adopt the meaningful learning of foreign languages is seen as exploiting the dynamics of interrelation between linguistic literary and inter cultural education BAGNO e RANGEL 2005 BALBONI 2008 2012 2018 BALBONI e CAON 2015 CAON e SPALIVIERO 2015 COSSON 2020 MENDES 2011 SPALIVIERO 2020 Starting from the concept of language as language-culture l ngua-cultura MENDES 2011 and of literature as a language and a repertoire COSSON 2020 we propose an analysis of Ondjaki s work H prendisajens com o x o o segredo h mido da lesma outras descoisas 2002 which is characterized by a strong dialogic component with the Brazilian Manoel de Barros s poetry illustrating how the construction of meaning takes place through the indissoluble interconnection between linguistic literary and cultural levels Study and reflection on the literary text is a tool to access this three-dimensionality of language and constitutes a precious opportunity for a language-culture insight experience for PFL Portuguese as a Foreign Language learners contributing to train them as foreign language specialists and helping to build them as individuals